Sequential MR Image‐Guided Local Immune Checkpoint Blockade Cancer Immunotherapy Using Ferumoxytol Capped Ultralarge Pore Mesoporous Silica Carriers after Standard Chemotherapy. Issue 52 (7th November 2019) - Choi, Bongseo; Jung, Huijin; Yu, Bo; Choi, Hyunjun; Lee, Joonseok; Kim, Dong‐Hyun
Abstract: Herein, ferumoxytol (Fer) capped antiprogrammed cell death‐ligand 1 (PD‐L1) antibodies (aPD‐L1) loaded ultralarge pore mesoporous silica nanoparticles (Fer‐ICB‐UPMSNPs) are formulated for a sequential magnetic resonance (MR) image guided local immunotherapy after cabazitaxel (Cbz) chemotherapy for the treatment of prostate cancer (PC). The highly porous framework of UPMSNP provides a large capacity for aPD‐L1. Fer capping of the pores extends the period of aPD‐L1 release and provides MR visibility of the aPD‐L1 loaded UPMSNP. As‐chosen Cbz chemotherapy prior to the local immunotherapy induces strong immunogenic cell death, dendritic cell maturation, and upregulation of PD‐L1 of tumor cells. Finally, tumor growth inhibition of sequential MR image‐guided local delivery of Fer‐ICB‐UPMSNPs and a tumor specific adoptive immune reaction are demonstrated in the pretreated Tramp C1 PC mouse model with Cbz chemotherapy. The tumor suppression is superior to those obtained with systemic ICB treatment after Cbz, only Fer‐ICB‐UPMSNP or only Cbz. As a proof‐of concept, MR image‐guided local ICB immunotherapy using Fer‐ICB‐UPMSNPs after chemotherapy suggests a new perspective of translational local immunotherapy for patients who are treated with standard chemotherapies. Abstract : Ferumoxytol capped antiprogrammed cell death‐ligand 1 (PD‐L1) antibodies (aPD‐L1) loaded ultralarge pore mesoporous silica nanoparticles are delivered with image guidance after cabazitaxel (Cbz) chemotherapy for the treatment of prostate cancer. A single session of sequential magnetic resonance image guided chemo‐immunotherapy effectively activates T cell infiltration, insisting tumor specific adaptive immunity and tumor rejection superior to systemic aPD‐L1 treatment after Cbz of the same dose.